The Influence of Organizational Justice on Employee Engagement is Mediated by Job Satisfaction at the Yogyakarta College of Aerospace Technology (STTKD) - Andarini, Siska; Wahyuni, Purbudi; Siswanti, Yuni (UPN Veteran Yogyakarta, 2024)
This study aims to analyze the effect of Organizational Justice on Employee Engagement Mediated by Job Satisfaction at the Sekolah Tinggi Teknologi Kedirgantaraan (STTKD) Yogyakarta. The type of research used is quantitative research. The population in this study was 159 employees, where the sample used was 114 employees. The data collection method in this study was a questionnaire measured by a Likert scale. The data analysis technique in this research is Path Analysis and Paired Sample Test on Permanent Employees and Contract Employees. The results of this study indicate that 1) There is a positive and significant effect of Organizational Justice variable on employee engagement at the STTKD Yogyakarta. 2) There is a positive and significant effect of Organizational Justice variable on Employee Engagement mediated by Job Satisfaction at the STTKD Yogyakarta. 3) There is a significant difference in employee engagement of permanent employees and non-permanent employees at the STTKD Yogyakarta.